2008
DOI: 10.1210/jc.2007-2432
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Differences in Children Born After in Vitro Fertilization: Follow-Up Study

Abstract: These findings highlight the importance of continued cardiometabolic monitoring of IVF-conceived children and might contribute to current knowledge about periconceptional influences and their consequences in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
244
2
19

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(285 citation statements)
references
References 26 publications
20
244
2
19
Order By: Relevance
“…Generally the data are ressuring, nevertheless a small but consistent increase in blood pressure of ART-children compared to children born after spontaneous conceptions has been found [78,79]. This in contrast to a recent study from Belgium that failed to confirm the difference in ICSI children [80].…”
Section: Norwegian Data On Art Children and Their Siblingsmentioning
confidence: 56%
“…Generally the data are ressuring, nevertheless a small but consistent increase in blood pressure of ART-children compared to children born after spontaneous conceptions has been found [78,79]. This in contrast to a recent study from Belgium that failed to confirm the difference in ICSI children [80].…”
Section: Norwegian Data On Art Children and Their Siblingsmentioning
confidence: 56%
“…Никаких разли-чий между этими двумя группами обнаружено не было [9]. Тем не менее у детей, зачатых с помощью ЭКО, выявлены более высокие цифры артериально-го давления и уровня глюкозы в крови по сравнению с той же возрастной группой (8-18 лет) из общей по-пуляции [10,11]. Также зафиксирована предраспо-ложенность к ожирению у детей, зачатых c помощью метода ИКСИ [4].…”
Section: заболеваемость раком после экоunclassified
“…For example, 22.5% of women report an episode of drinking during the first month of gestation but not later in pregnancy (Ethen et al 2009), whilst many women alter their diet or begin taking dietary supplements when knowingly pregnant (Elmadfa & Meyer 2012). Studies into long-term health of babies from assisted reproductive technologies have shown that children born following IVF have higher systolic and diastolic blood pressure, as well as higher fasting blood glucose levels (Ceelen et al 2008). This suggests that manipulation of the embryo around the time of conception can alter development and can have long-lasting effects.…”
Section: Human Periconceptional Exposuresmentioning
confidence: 99%